Pengembangan LKPD Berbasis Model Problem Based Learning pada Materi Perbandingan untuk memfasilitasi Kemampuan Pemecahan Masalah Matematis Siswa Fase D - Octia Madeyenti Darmawan; Syofni; Sakur (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study is a development research aimed at producing valid and practical worksheets (LKPD) on the topic of phase comparison D. The background of this research is students' low mathematical problem-solving abilities and the importance of worksheets that facilitate students' mathematical problem-solving abilities. The development model used is the 4-D development model (define, design, develop, and disseminate). The define phase consists of initial and final analysis, student analysis, task analysis, concept analysis, and learning objective specifications. The design phase involves designing the product: the LKPD, validation sheets, and student response questionnaires. The next phase, development, involves validation by three validators, with the average validation percentage of the LKPD being 85.91% in the "very valid" category. Subsequently, a small group trial was conducted with 6 junior high school students, resulting in an average percentage of 87.17% in the "very practical" category. A large group trial was conducted with 38 seventh-grade junior high school students, resulting in an average percentage of 81.91% in the "practical" category. The product was packaged and disseminated in the dissemination phase by providing the developed product to schools. In this study, worksheets based on the Problem-Based Learning model on comparison have met the criteria of validity and practicality.